Highly efficient short length Bismuth-based erbium-doped fiber amplifier - Cheng, Xiau S.; Hamida, Belal Ahmed; Arof, Hamzah; Ahmad, Harith; Harun, Sulaiman Wadi (IOP Publishing, 2011)
An efficient 21 cm Bismuth-based erbium doped fiber amplifier (Bi-EDFA) operating in both C- and L-band wavelength regions is proposed and demonstrated. The proposed Bi-EDFA uses the gain medium with an erbium ion concentration of 6300 ppm in conjunction with a double-pass configuration. Compared to conventional silica-based erbium-doped fiber amplifiers (Si-EDFAs) with the same amount of Erbium ions, the Bi-EDFA provides a higher attainable gain as well as a greater amplification bandwidth ranging from 1525 to 1620 nm. The proposed Bi-EDFA achieved a flat-gain of around 23 dB with gain variation of ±3.5 dB within the wavelength region from 1530 to 1565 nm at the maximum pump power of 150 mW. The corresponding noise figures are obtained at an average of 6 dB.